Rapid determination of influenza vaccine potency by an SPR-based method using subtype or lineage-specific monoclonal antibodies - Narayan, Kartik; Paduraru, Crina; Blake, Taylor; Arunachalam, Arun B. (Frontiers in Immunology, 2023)
Potency testing and release of annual influenza vaccines require preparation, calibration, and distribution of reference antigens (RAs) and antisera every year, which takes an average of 8 to 12 weeks, and can be a major limiting factor in pandemic situations. Here we describe for the first time a robust Surface Plasmon Resonance (SPR)-based method that employs influenza subtype or lineage hemagglutinin (HA) specific monoclonal antibodies (mAbs) to measure the HA concentration in influenza multivalent vaccines. Implementing such an advanced test method will at the very least eliminate the rate-limiting and laborious efforts of making antisera reagents annually, and thus expedite the influenza vaccine delivery to the public by at least 6 weeks. Results demonstrate that the SPR-based method, developed using Biacore, is robust and not influenced by the type of RAs (inactivated whole virus, split, or subunit vaccine-derived materials), whether they are used as monovalent or multivalent preparations. HA concentrations obtained for monovalent drug substances (DS) or quadrivalent drug products (DP) of inactivated influenza split vaccine showed a tight correlation (the best fit value for the slope is 1.001 with R2 of 0.9815 and P-value <0.0001) with the corresponding values obtained by the current potency assay, Single Radial Immunodiffusion (SRID). Supplementary analysis of the results by the Bland-Altman plot demonstrated good agreement between the SPR and SRID methods, with no consistent bias of the SPR versus SRID method. We further demonstrate that the SPR-based method can be used to estimate HA concentrations in intermediates of the influenza vaccine manufacturing process containing varying matrices and impurity levels. Further, the results demonstrate that the method is sensitive to detecting degradation of HA caused by elevated temperature, low pH, and freezing. It is evident from this report and other published work that the advancement of analytical techniques and the early findings are encouraging for the implementation of alternate potency assays with far-reaching benefits covering both seasonal and pandemic influenza.